# Solve the following equation for x

$\dfrac{18\left( 7x-3 \right)}{2x+1}=\dfrac{250\sqrt{2x+1}}{3\sqrt{7x-3}}$

Last updated date: 15th Mar 2023

•

Total views: 303.3k

•

Views today: 8.82k

Answer

Verified

303.3k+ views

Hint: Square both sides to get and substitute $\dfrac{7x-3}{2x+1}=t$. Take care of extraneous roots which will be due to the quantity inside the square root is $\ge 0$ and denominator of each fraction $\ne 0$. Remove those values at which the above conditions are not satisfied.

Let $t=\dfrac{7x-3}{2x+1}$

So, we have

$\begin{align}

& \dfrac{18\left( 7x-3 \right)}{2x+1}=\dfrac{250\sqrt{2x+1}}{3\sqrt{7x-3}} \\

& \Rightarrow \dfrac{18\left( 7x-3 \right)}{2x+1}=\dfrac{250}{3}\sqrt{\dfrac{2x+1}{7x-3}} \\

& \Rightarrow \dfrac{18\left( 7x-3 \right)}{2x+1}=\dfrac{250}{3\sqrt{\dfrac{7x-3}{2x+1}}} \\

& \Rightarrow 18t=\dfrac{250}{3\sqrt{t}} \\

\end{align}$

Cross multiplying, we get

$54{{t}^{\dfrac{3}{2}}}=\dfrac{250}{3}$

Dividing both sides by 54 we get

$\begin{align}

& \dfrac{54{{t}^{\dfrac{3}{2}}}}{54}=\dfrac{250}{3\times 54} \\

& \Rightarrow {{t}^{\dfrac{3}{2}}}=\dfrac{125}{81} \\

& \Rightarrow {{t}^{\dfrac{3}{2}}}={{\left( \dfrac{5}{3} \right)}^{3}} \\

& \Rightarrow t={{\left( \dfrac{5}{3} \right)}^{3\times \dfrac{2}{3}}} \\

& \Rightarrow t={{\left( \dfrac{5}{3} \right)}^{2}} \\

& \Rightarrow t=\dfrac{25}{9} \\

& \Rightarrow \dfrac{7x-3}{2x+1}=\dfrac{25}{9} \\

\end{align}$

Cross multiplying, we get

$9\left( 7x-3 \right)=25\left( 2x+1 \right)$

Simplifying we get

$63x-27=50x+25$

Transposing 27 to RHS and 50x to LHS we get

$63x-50x=25+27$

Simplifying we get

$13x=52$

Dividing both sides by 13, we get

$\dfrac{13x}{13}=\dfrac{52}{13}$

x = 4

Also, we need to check if the terms under square root are non-negative

We have $7x-3=28-3=25\ge 0$ which satisfies the condition

$2x+1=8+1=9\ge 0$ which also satisfies the condition

Also, we need to check that the terms in the denominator are not equal to 0

Since 2x+1 = 9 and 7x – 3 = 25 are both not equal to 0 we have all the conditions satisfied.

Hence x = 4 is the root of the equation $\dfrac{18\left( 7x-3 \right)}{2x+1}=\dfrac{250\sqrt{2x+1}}{3\sqrt{7x-3}}$

Note: [1] Verification: $\dfrac{18\left( 7x-3 \right)}{2x+1}=\dfrac{18\times 25}{9}=50$

$\dfrac{250\sqrt{2x+1}}{3\sqrt{7x-3}}=\dfrac{250\sqrt{9}}{3\sqrt{25}}=\dfrac{250\times 3}{3\times 5}=50$

Hence $\dfrac{18\left( 7x-3 \right)}{2x+1}=\dfrac{250\sqrt{2x+1}}{3\sqrt{7x-3}}$.

Hence it is verified that x = 4 is the root of the given equation.

[2] Substitution of $t=\dfrac{7x-3}{2x+1}$ was the primary step in solving the question. It reduced the effort in solving the question. Substitutions usually help in solving equations faster. e.g. we can solve the question $\left( x+3 \right)\left( x+4 \right)\left( x+5 \right)\left( x+6 \right)=100$ by expanding and forming a biquadratic and solving that biquadratic which would be very difficult or by substituting ${{x}^{2}}+9x+18=t$ in which case we have

$\left( x+3 \right)\left( x+4 \right)\left( x+5 \right)\left( x+6 \right)=\left[ \left( x+3 \right)\left( x+6 \right) \right]\left[ \left( x+5 \right)\left( x+4 \right) \right]$

= $\left( {{x}^{2}}+9x+18 \right)\left( {{x}^{2}}+9x+20 \right)=t\left( t+2 \right)=\text{ }100$

In this case, it is equivalent to solving two quadratic equations and is much easier than solving the biquadratic equation.

__Complete step-by-step solution -__Let $t=\dfrac{7x-3}{2x+1}$

So, we have

$\begin{align}

& \dfrac{18\left( 7x-3 \right)}{2x+1}=\dfrac{250\sqrt{2x+1}}{3\sqrt{7x-3}} \\

& \Rightarrow \dfrac{18\left( 7x-3 \right)}{2x+1}=\dfrac{250}{3}\sqrt{\dfrac{2x+1}{7x-3}} \\

& \Rightarrow \dfrac{18\left( 7x-3 \right)}{2x+1}=\dfrac{250}{3\sqrt{\dfrac{7x-3}{2x+1}}} \\

& \Rightarrow 18t=\dfrac{250}{3\sqrt{t}} \\

\end{align}$

Cross multiplying, we get

$54{{t}^{\dfrac{3}{2}}}=\dfrac{250}{3}$

Dividing both sides by 54 we get

$\begin{align}

& \dfrac{54{{t}^{\dfrac{3}{2}}}}{54}=\dfrac{250}{3\times 54} \\

& \Rightarrow {{t}^{\dfrac{3}{2}}}=\dfrac{125}{81} \\

& \Rightarrow {{t}^{\dfrac{3}{2}}}={{\left( \dfrac{5}{3} \right)}^{3}} \\

& \Rightarrow t={{\left( \dfrac{5}{3} \right)}^{3\times \dfrac{2}{3}}} \\

& \Rightarrow t={{\left( \dfrac{5}{3} \right)}^{2}} \\

& \Rightarrow t=\dfrac{25}{9} \\

& \Rightarrow \dfrac{7x-3}{2x+1}=\dfrac{25}{9} \\

\end{align}$

Cross multiplying, we get

$9\left( 7x-3 \right)=25\left( 2x+1 \right)$

Simplifying we get

$63x-27=50x+25$

Transposing 27 to RHS and 50x to LHS we get

$63x-50x=25+27$

Simplifying we get

$13x=52$

Dividing both sides by 13, we get

$\dfrac{13x}{13}=\dfrac{52}{13}$

x = 4

Also, we need to check if the terms under square root are non-negative

We have $7x-3=28-3=25\ge 0$ which satisfies the condition

$2x+1=8+1=9\ge 0$ which also satisfies the condition

Also, we need to check that the terms in the denominator are not equal to 0

Since 2x+1 = 9 and 7x – 3 = 25 are both not equal to 0 we have all the conditions satisfied.

Hence x = 4 is the root of the equation $\dfrac{18\left( 7x-3 \right)}{2x+1}=\dfrac{250\sqrt{2x+1}}{3\sqrt{7x-3}}$

Note: [1] Verification: $\dfrac{18\left( 7x-3 \right)}{2x+1}=\dfrac{18\times 25}{9}=50$

$\dfrac{250\sqrt{2x+1}}{3\sqrt{7x-3}}=\dfrac{250\sqrt{9}}{3\sqrt{25}}=\dfrac{250\times 3}{3\times 5}=50$

Hence $\dfrac{18\left( 7x-3 \right)}{2x+1}=\dfrac{250\sqrt{2x+1}}{3\sqrt{7x-3}}$.

Hence it is verified that x = 4 is the root of the given equation.

[2] Substitution of $t=\dfrac{7x-3}{2x+1}$ was the primary step in solving the question. It reduced the effort in solving the question. Substitutions usually help in solving equations faster. e.g. we can solve the question $\left( x+3 \right)\left( x+4 \right)\left( x+5 \right)\left( x+6 \right)=100$ by expanding and forming a biquadratic and solving that biquadratic which would be very difficult or by substituting ${{x}^{2}}+9x+18=t$ in which case we have

$\left( x+3 \right)\left( x+4 \right)\left( x+5 \right)\left( x+6 \right)=\left[ \left( x+3 \right)\left( x+6 \right) \right]\left[ \left( x+5 \right)\left( x+4 \right) \right]$

= $\left( {{x}^{2}}+9x+18 \right)\left( {{x}^{2}}+9x+20 \right)=t\left( t+2 \right)=\text{ }100$

In this case, it is equivalent to solving two quadratic equations and is much easier than solving the biquadratic equation.

Recently Updated Pages

If a spring has a period T and is cut into the n equal class 11 physics CBSE

A planet moves around the sun in nearly circular orbit class 11 physics CBSE

In any triangle AB2 BC4 CA3 and D is the midpoint of class 11 maths JEE_Main

In a Delta ABC 2asin dfracAB+C2 is equal to IIT Screening class 11 maths JEE_Main

If in aDelta ABCangle A 45circ angle C 60circ then class 11 maths JEE_Main

If in a triangle rmABC side a sqrt 3 + 1rmcm and angle class 11 maths JEE_Main

Trending doubts

Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Write the 6 fundamental rights of India and explain in detail

Write a letter to the principal requesting him to grant class 10 english CBSE

List out three methods of soil conservation

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Epipetalous and syngenesious stamens occur in aSolanaceae class 11 biology CBSE